Specific TaqMan probed real-time quantitative RT-PCR methods and their application to differentiate the transcripts of duplicated BF or BLB genes in chicken MHC - Cai-Xia Gao; Lingxia Han; Liandong Qu; Yu-Zhu Luo; Han Jianlin (Elsevier, 2012)
BF and BLB genes of chicken major histocompatibility complex (MHC) are responsible for classical antigen processing and presentation; therefore they play a central role in determining the genetic resistance or susceptibility of different MHC haplotypes to some infectious diseases. In this study, we developed specific TaqMan probed real-time quantitative reverse transcription PCR (TaqMan qRT-PCR) methods based on the diagnostic nucleotide polymorphisms present in duplicated BF or BLB genes in B2 and B19 haplotypes. The results showed very similar amplification efficiency but no cross-reaction between the duplicated BF or BLB genes of the same haplotype. Spleen mRNA samples of B2 and B19 chickens were used to validate these TaqMan qRT-PCR methods. We observed that BF2 or BLB2 gene was dominantly transcribed in all B2 and B19 chickens. Our findings verified the impact of diversified promoter sequences on the function of duplicated BF or BLB genes. Hence the principles adopted to establish these specific TaqMan qRT-PCR methods in this study can be applied to differentiate the transcripts of duplicated BF or BLB genes of other MHC-B haplotypes in chicken.